A Controversial Warplane: Narratives, Counternarratives, and the Italian Debate on the F-35. (November 2016) - Coticchia, Fabrizio
The literature on strategic narratives has started to pay growing attention to the concept of "narrative dominance, " stressing the role played by counternarratives in hindering a wider acceptance of a specific message. However, limited consideration has been devoted to counternarratives, which have seldom been assessed in a systematic way. The aim of this article is to fill these gaps by examining the underrated case of Italy. The article investigates the main content of narratives and counternarratives developed by parties and peace movements regarding the decision to acquire the F-35. The article, which is based on primary and secondary sources, adopts a multidisciplinary approach, combining security studies and social movement studies.